Loss of synthesis of modern architecture and art in Istanbul: case of Izzet Sefizade Villa - Ciftci, Aynur (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
The changing urban texture of Istanbul saw the construction of qualified houses, especially in the summer house districts, during the rise of modernist architecture after the 1950s. The Izzet Sefizade Villa built in 1961 in Fenerbahce, a popular summer destination, is an undocumented example of the synthesis between modern architecture and art with its wall mosaic made by Ferruh Basaga (1914-2010), an important representative of Turkish abstract art. Despite its technical, aesthetic and social value, the building was found under earthquake risk and demolished in 2018 rather than being reinforced, and a new public center was built. This article discusses the loss of the building from the perspectives of urban transformation and conservation, the synthesis of architecture and art, and urban memory. As a rare and informative example, it shows that it is possible to save art works or architectural elements which are afforded no protection by law or ordinances.
Keywords: Modern architecture; art; Istanbul; wall mosaic; conservation; Ferruh Basaga; Architecture